Answer:
1000 seconds = 1 million milliseconds
1000 seconds = 16.67 minutes
1000 seconds = 0.28 hour
Step-by-step explanation:
Given
1,000 seconds
Required:
Convert to similar units
The given parameters is a unit of time.
Other units of time are
1. Milliseconds
2. Minutes.
3. Hour
And lots more
We'll convert the given time to the above time units but first, take note of the following
1. 1 seconds = 1000 millisecond
2. 60 seconds = 1 minutes
3. 3600 seconds = 1 hour
To convert the time in seconds to milliseconds, we make use of (1) above
If 1 seconds = 1000 milliseconds, we calculate 1000 seconds by multiplying both sides of the equation by 1000
So, we have
1 seconds * 1000 = 1000 milliseconds * 1000
1000 seconds = 1 million milliseconds
To convert the time in seconds to minutes, we make use of (2) above
If 60 seconds = 1 minutes, we calculate 1000 seconds by multiplying both sides of the equation by 1000/60
So, we have
60 seconds * 1000/60 = 1 minute * 1000/60
1000 seconds = 1000/60 minutes
1000 seconds = 16.67 minutes
To get this time in hours, we make use of (3)
If 3600 seconds = 1 hour, we calculate 1000 seconds by multiplying both sides of the equation by 1000/3600
So, we have
3600 seconds * 1000/3600 = 1 hour * 1000/3600
1000 seconds = 1000/3600 hour
1000 seconds = 0.28 hour
Answer:
-8/5 is the slope.
Step-by-step explanation:
To find slope, it's the change in y over the change in x. Or rise over run.
That would be 8/5.
And this line would be negative because it is going from left to right.
So your final answer would be -8/5 as your slope.
Answer:
1. 64
2. 81
3. 25
4. 27
5. 63
6. 27
7. 22
8. 16
9. 41
10. 25
11. 8
12. 24
13. 90
14. 24
15. 30
16. 38
17. 51
18. 18
19. 33
20. 12
21. 17
22. 28
23. 70
24. 67
25. 13
26. 20
3(x - 2) - 5x = 18
The required simplifiedvalue of the x for the given expression is -2.
Given that,
To determine the value of the x for the expression 3(x - 2) - 5x = 18.
The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.
Here,
3(x - 2) - 5x = 18
Simplifying the above equation,
3x - 6 - 5x = 18
3x - 5x = 18 + 6
-2x = 24
x = 24 / -2
x = -12
Thus, the required simplifiedvalue of the x for the given expression is -2.
Learn more about simplification here: brainly.com/question/12501526
#SPJ2